Financial policy in an exuberant world - Ansgar Walther (European Central Bank (ECB), 2020)
This paper studies optimal financial policy in a world where the financial sector can become excessively optimistic. I decompose the welfare effects of bank capital regulation to demonstrate the effects of exuberance and its interaction with incentive problems in banking. The optimal policy depends not only on the extent, but also on the type of optimism. For example, it is markedly different when the exuberance of banks focuses on neglected downside risk, as opposed to overstated upside opportunities. A central normative conclusion is that "leaning against the wind", by tightening capital requirements in exuberant times, can be counterproductive. I show that two natural metrics, describing the distortion in perceived upside and downside risk, are sufficient statistics for the policy implications of exuberance. My results shed light on the diverse empirical evidence on the relationship between bank capital and risk-taking. Finally, I investigate the sensitivity of these insights under different assumptions about government rationality and paternalism.
Keywords: G01; G21; G40; 330; Financial crises; banking; behavioral finance; macroprudential policy